Recent Advances in the Microencapsulation of Essential Oils, Lipids, and Compound Lipids through Spray Drying: A Review - Diego Mauricio Sánchez-Osorno; María Camila López-Jaramillo; Angie Vanesa Caicedo Paz; Aída Luz Villa; María S. Peresin; Julián Paul Martínez-Galán (MDPI AG, 2023)
In recent decades, the microcapsules of lipids, compound lipids, and essential oils, have found numerous potential practical applications in food, textiles, agricultural products, as well as pharmaceuticals. This article discusses the encapsulation of fat-soluble vitamins, essential oils, polyunsaturated fatty acids, and structured lipids. Consequently, the compiled information establishes the criteria to better select encapsulating agents as well as combinations of encapsulating agents best suited to the types of active ingredient to be encapsulated. This review shows a trend towards applications in food and pharmacology as well as the increase in research related to microencapsulation by the spray drying of vitamins A and E, as well as fish oil, thanks to its contribution of omega 3 and omega 6. There is also an increase in articles in which spray drying is combined with other encapsulation techniques, or modifications to the conventional spray drying system.